The Influence of Principal Leadership and Teachers’ Job Satisfaction on Teachers’ Performance at State Elementary School - Risnayanti Risnayanti; Yasir Arafat; Syaiful Eddy (Journal of Social Work and Science Education, 2027)
This study aims to determine the influence of principal leadership and teacher job satisfaction on teacher performance in public elementary schools within the Kalidoni sub-district of Palembang. A quantitative approach was employed, with data collected through questionnaire distribution to respondents across 7 public elementary schools. The sample comprised 104 teachers, determined using Slovin's formula. Data were analyzed using multiple regression analysis, incorporating t-tests, F-tests, and coefficient of determination. The findings reveal that: (1) principal leadership has a significant partial influence on teacher performance; (2) teacher job satisfaction has a significant partial influence on teacher performance; and (3) both principal leadership and teacher job satisfaction simultaneously exert a significant influence on teacher performance, confirming that these two variables jointly predict performance outcomes. This study provides empirical evidence from an urban sub-district context in Palembang, demonstrating the combined predictive power of leadership and job satisfaction on teacher performance in a multi-school setting, an area relatively underexplored in local educational research. Findings underscore the necessity for school principals and district policymakers to simultaneously prioritize leadership development and teacher welfare programs to sustain and enhance performance. This research contributes actionable insights for educational administrators, affirming that teacher performance is optimized when strong leadership is complemented by high job satisfaction, offering a foundational reference for performance improvement strategies in urban elementary school contexts.